Etude de la structure spatiale et dendrométriques de Chrysophyllum lacourtianum (De Wild) et Chrysophyllum africanum (A. DC) Dans la réserve forestière de Yangambi. (RD. Congo) - Vanyle ISUMA LINGOLE; Alexadre Delvaux LOFOLI TABU; Albert ANGBONGA BASIA; Dimanche YENGA BOMBEKU; Addhhee ATAKEA BOTIKOTIKO; Nestor MOLANGA BAKATOKANA; Joseph BONDELE; Junior LIOTHO LITENASONGO; Fiston RAMAZANI ADJONGO; Nestor BASANGALELO LOKUTU; Fiston LOFOLI TSHOMA; Laurent BAMBALE BOTANDO, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The study of the spatial and dendrometric structure of two species describes the organization and the quantity of these species comparatively, following biological and ecological mechanisms influencing the growth of these species within a zone data for a lasting management. In the natural reserve of Biosphere of Yangambi a device of 20 ha, that to be-to-say of 200 m x 1000 m was installed in which a systematic inventory of Chrysophyllum lacourtianum and Chrysophyllum africanum measured to 10 cm of DBH has been geographical positioned by a X abscissa and an ordered Y. The spatial distribution of our gases has been analyzed with the help of the K function of Ripley, one also uses the L function (r). The spatial distribution of these two species analyzed on Past software has been judged globally uncertain in accordance with the projection of geo-referencing points, one observes between 7 and 20 an aggregation for Chrysophyllum africanum. The species Chrysophyllum africanum presents a decreasing geometric progression (a pace in shape of J reversed) whereas the superior dbh classes to 50-60 cm are not represented, Chrysophyllum lacourtianum presents individuals in all diametric classes with a weak variation between frequencies of stems presenting a pace in "S stretched". The species Chrysophyllum africanum is slightly dense with an average of 3,1 tree/ha and invading month soil with an average of 0.167 m²/ha of surface terriere. On the other hand, Chrysophyllum lacourtianum has a middle density of 3 tree/has and an average of 0.724 m²/ha of terriere surface occupying soil more.